Analysis of South Coast Marine Tourism Development in Jember Regency Using the Recreation Opportunity Spectrum Method - Kamal, Mushthofa; Suharsono, Degita Danur; Taufan, Gullit Tornado; Haikal, Fadlan Arif; Prismadani, Shinta Dwi (Journal of Language, Communication, and Tourism, 2024)
Marine tourism is a natural tourism activity that takes place in coastal areas which includes beach, seascape, and sea underwater. The development of marine tourism destinations in the southern coastal area of Jember Regency is urgently needed especially to the areas with promising prospects like Papuma and Watu Ulo beaches which are known to be located in the Blue Diamond area. Through the Recreation Opportunity Spectrum (ROS) method, it is expected that a framework can be designed to identify the opportunity of an area to become a tourist attraction. In the ROS analysis process, there are four criteria that become parameters, which are: experience, environment, location, and example of activities. The purpose of this research is to identify the recreational zones in planning that does not conflict with the principles of marine area management. This research uses a qualitative descriptive method approach. The result of this research is that Papuma Beach falls into the category of class II Semi-Primitive Motorized and Watu Ulo Beach in the category of class III Roaded Natural.